PENGARUH PERUBAHAN TARIF PAJAK, PROFITABILITAS DAN LIKUIDITAS TERHADAP PAJAK MELALUI DEBT TO EQUITY RATIO (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2007-2011) (Students' Journal of Economic and Management, 2013)
The purpose of this study to test empirically and analyze the influence of Tax Rate Change, Profitability and Liquidity of the Income Corporate Taxes through the DER. This study examined again Azfa research and Hussain (2011) as opposed to Mallikarjunappa and Goveas (2007) and opposed by Sabir and Malik (2012). The difference lies in the study sample and variables used as well as research models. The study was conducted at the manufacturing companies listed on the Stock Exchange for the year 2007-2011 according to data ICMD 2012, there were an average of 47,3% of manufacturing companies who have a DER> 1 and indicated by the thin capitalization practice in an attempt to tax avoidance. This study uses a sample of 456 firm-years observation companies were selected using purposive sampling method. Examination of the relevant literature has been developed to generate a path analysis model. Hypothesis consists of four hypotheses and tested using SPSS 20 program. The results showed that the profitability and tax rate change had significant effect for DER, while the liquidity does not affect the DER but in terms of corporate tax, DER had positive and does not significant affect on it Keywords:  Tax rate change, profitability, liquidity, DER and income corporate tax